Length-Weight Relationship and Condition Factor of Stingray Himantura uarnacoides Landed at TPI Dumai Riau Province, Indonesia - Sibagariang, Rina D; Mulyani, Isma; Lesmana, Indra (Jurnal Perikanan dan Kelautan, 2024)
Stingrays are a type of fish that has experienced a reasonably high population decline in nature due to their relatively low reproduction, overfishing, and habitat degradation, so it is feared that they could become extinct. This study analyses the length-weight relationship, condition factors, and growth patterns of Himantura uarnacoides stingrays landed at TPI Dumai Riau Province. This study was conducted in May–July 2023 and June–July 2024. The number of samples analyzed was 48 (24 females and 24 males). The results showed that the length of H. uarnacoides stingrays that landed at TPI Dumai ranged from 32.5–78 cm. The smallest fish size was in the 27.5–35.5 cm class range. The size of the fish most often caught was in the 51.5–59.5 cm class range. The highest condition factor value of 1.40 was found in the 28–25 cm class range. The length-weight relationship shows the equation W = 0.000059L2.869 with a coefficient of determination (R²) value of 0.911. The growth pattern of the H. uarnacoides stingray is negative allometric